The Mechanism and Function of Glia in Parkinson's Disease - Zhang, Xinguo; Zhang, Ruiqi; Nisa Awan, Maher Un; Bai, Jie (Frontiers in Cellular Neuroscience, 2022)
Parkinson's disease (PD) is a neurodegenerative disease that primarily affects elderly people. The mechanism on onset and progression of PD is unknown. Currently, there are no effective treatment strategies for PD. PD is thought to be the loss of midbrain dopaminergic neurons, but it has recently been discovered that glia also affects brain tissue homeostasis, defense, and repair in PD. The neurodegenerative process is linked to both losses of glial supportive-defensive functions and toxic gain of glial functions. In this article, we reviewed the roles of microglia, astrocytes, and oligodendrocytes in the development of PD, as well as the potential use of glia-related medications in PD treatment.